STUDENTS’ COMPETENCE IN WRITING A DISCUSSION GENRE - Parman Hasibuan (JEE (Journal of English Education), 2015)
This research has the students’ difficulties in writing a Discussion genre as its background. Meanwhile, the draft of the 2004 English curriculumsuggests that the teaching of writing to senior high school students should be enhanced. This research was intended to investigate the students’ competence in writing a Discussion genre, a text type in English. This research was conducted in two phases at one senior high school in Rokan Hulu, Riau province. There were nine participants involved in this study. They were all from the twelfth year. This research was a qualitative case study in nature, since it dealt with a holistic description and text analysis. The procedures used to collect data were observation, interview, and writing test. For analysing students’ texts, Systemic functional grammar (SFG) was used as a tool. The findings revealed that the students develop their competence in writing a Discussion genre quite slowly. Their writing development started from recognizing a Discussion genre through its schematic structure, linguistic features, and metaphorical expressions. Next, they understood how to develop arguments in argument stages. They have used some linguistic features, such as one of the most controversial issues, the proponents of, the opponents of, in conclusion in their Discussion genre texts. This indicates that they have tried to produce coherent texts, particularly in terms of generic coherence. In terms of building internal properties of the text, one student had used good structural Themes. Finally, there was an improvement in self-confidence, as marked by the ability to produce longer texts, which averagely contain 408 words. Meanwhile in terms of weaknesses, the students still got problems dealing with grammatical patterns, cohesion, coherence, and dictions to support the clarity and effectiveness of sentences. They also had difficulties in developing arguments with convincing evidence. After looking at the findings above, the researcher believes that the teaching cycles as suggested in Genre-based approach are still possible to be adopted in the teaching of writing, particularly the Discussion genre. Finally, realizing that this research is far from perfect, the writer invites all concerned people to do similar research to improve the quality of the findings in this study.